RUWATAN DALAM BUDAYA JAWA - S. Reksosusilo (Studia Philosophica et Theologica, 2006)
Ruwatan is an old Javanese ceremony for the purposes of lifting a curse, washing up impending danger, or neutralizing the harmful of evil powers inherent in certain events or situations. These customs are already known by the time of Majapahit periods as kown by literature and temple’s reliefs in that time. The old customs consist of telling “Ruwatan” stories (like the Sudamala). But contemporary Javanese for the “Ruwatan” perform the ruwatan Wayang Lakon Murwakala. We expose in this article those “Ruwatan” performance, and reflect on them, in order to get the deeper meaning of ruwatan in the Javanese culture.